A framework for mapping cultural resources in landscape conservation planning. Issue 6 (3rd May 2019) - Ogletree, S. Scott; Powell, Robert B.; Baldwin, Robert F.; Leonard, Paul B.
Abstract: Cultural resources can be an important means of connecting people to conservation efforts. Currently, it is difficult to identify and map these tangible and intangible aspects of the landscape. We propose a framework to include cultural resources in spatial conservation planning that acknowledges the different scales of importance and management of sites. Through categorizing and mapping sites of national, state, local, interest group, and community management, cultural resources can be measured and included in existing planning tools. Data on cultural resources are a primary limitation due to availability and fragmentation. Until data sources improve, our framework provides a stopgap that allows for cultural resources to be included in conservation‐planning efforts.